PENGARUH PREDIKSI KEBANGKRUTAN, DEBT DEFAULT, DAN KONDISI KEUANGAN TERHADAP OPINI GOING CONCERN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE TAHUN 2016-2018 - Muhammad Sofyan; Noor Shodiq Askandar; Abdul Wahid Mahsuni (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTGoing concern audit opinion is the opinion issued by the auditor to ensure whether the company can maintain survival. Going concern audit opinion can be used as an initial warning for users of financial statements regarding the factors that influence the going concern audit opinion that has been carried out. This study aims to examine the effect of bankruptcy debt default prediction, and financial conditions on going-concern audit opinion. This study uses manufacturing companies listed on the Stock Exchange in the period 2016-2018, by purposive sampling method obtained 26 samples. The results of this study indicate that the independent variable predictions of bankruptcy, and debt default affect the going concern opinion, while the financial condition does not affect the going concern opinion.Keywords: Bankruptcy Prediction, Default Debt, Financial Conditions, and Going Concern Opinion